Anti-Phospholipase A2 Receptor Antibody Expression at Different Stages of Idiopathic Membranous Nephropathy - Fu, Keying; Zhang, Pei; Han, Yeguang; Wang, Ru; Cai, Junhong (International Journal of Nephrology, 2022)
The significance of blood anti-phospholipase A2 receptor (PLA2R) antibodies in the diagnosis of different stages of idiopathic membranous nephropathy (IMN) was investigated. The expression and distribution of anti-PLA2R antibodies in renal biopsy tissue of patients with different stages of IMN were examined by immunohistochemistry. In addition, blood anti-PLA2R antibodies were determined by indirect immunofluorescence for the same patients, and the results were compared with the anti-PLA2R antibody expression in renal biopsy tissue. The positive fluorescence intensities of IMN stages I, IV, and V were mostly ± or + (40/80). There was no significant difference in fluorescence titer between these stages (p>0.05). These results were consistent with the immunohistochemistry results, and the kappa statistic was 0.95. The positive fluorescence intensities of IMN stages II and III were mostly ++ to ++++ (33/60). There was no significant difference in fluorescence intensities between these two stages (p>0.05), but there was a significant difference in fluorescence intensities between stages II and III and stages I, IV, and V (p<0.001). These results were consistent with the immunohistochemistry results, and the kappa statistic was 0.97 (p<0.001). Therefore, blood anti-PLA2R levels were positively correlated with anti-PLA2R expression in renal biopsy tissue in patients with different stages of IMN. In addition, the fluorescence intensities of IMN stages II and III were significantly different from those of stages I, IV, and V. Therefore, blood anti-PLA2R levels can be used for in vitro differential diagnosis and the monitoring of treatment, as it can distinguish stage II; and III; from stage I, IV, and V IMN.